Impact of Gestalt and Reality Counseling on Reducing Junior High School Students’ Anger in Social Media - Marpaung, Julia Vika Andriani; Muslihati, Muslihati; Hitipeuw, Imanuel; Valdez, V. (citeus, 2025)
Adolescent emotional development can be enhanced by effectively managing conflicts in everyday life, such as those encountered on social media. This study aims to evaluate the effectiveness of Gestalt group counseling with Rehearsal techniques and Reality group counseling with Expressive Writing techniques in mitigating anger emotions in students' social media interactions. Conducted as an experimental research with a pre-test-post-test two-treatment design, the study utilized purposive sampling to select 16 eighth-grade students from State Junior High School 2 Wagir, Malang Regency, Indonesia who demonstrated high levels of anger in social media. The participants were divided into two groups: one receiving Gestalt group counseling with Rehearsal techniques and the other Reality group counseling with Expressive Writing techniques. Data on anger emotions were collected using a specific anger instrument and analyzed with a t-Test. The findings indicate that: (1) Gestalt group counseling with Rehearsal techniques is effective in reducing anger emotions in students on social media; (2) Reality group counseling with Expressive Writing techniques is effective in reducing anger emotions in students on social media; (3) Gestalt group counseling with Rehearsal techniques is more effective than Reality group counseling with Expressive Writing techniques in reducing anger emotions in students on social media. The outcomes of this research may provide school counselors and researchers with additional references for the application of Gestalt group counseling in reducing anger emotions in social media among students.